1992
DOI: 10.1111/j.1432-1033.1992.tb19848.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure and orientation of the surfactant‐associated protein C in a lipid bilayer

Abstract: The secondary structure of native and depalmitoylated porcine surfactant-associated protein C (SP-C) was studied by attenuated total reflection Fourier-transform infrared spectroscopy. Both forms of porcine SP-C adopt mainly an alpha-helical conformation. These two forms of the protein were reconstituted in a lipid bilayer. The insertion of the protein in a membrane is associated with an increase of the alpha-helical content. Dichroic measurements show that, in both cases, the long axis of the alpha-helix is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
145
1

Year Published

1995
1995
2005
2005

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 181 publications
(169 citation statements)
references
References 49 publications
(4 reference statements)
23
145
1
Order By: Relevance
“…The FTIR spectrum of KL4 in DPPC/PG 7:3 (w/w) bilayers shows a peak maximum at 1656 cm -1, in the spectral region associated with helical structure. Deconvolution and curve fitting between 1700 cm -1 and 1600 cm -1 [8,12,23] yields 84% of a-helices for lipid-associated KL4. KL4 is helical also in non-lipid environments; in trifluoroethanol it gives a CD spectrum which is similar to that obtained in DPC micelles, and FTIR spectroscopy of KL4 alone, i.e.…”
Section: Secondary Structure Of Kl4 In Phospholipid Micellesmentioning
confidence: 99%
See 2 more Smart Citations
“…The FTIR spectrum of KL4 in DPPC/PG 7:3 (w/w) bilayers shows a peak maximum at 1656 cm -1, in the spectral region associated with helical structure. Deconvolution and curve fitting between 1700 cm -1 and 1600 cm -1 [8,12,23] yields 84% of a-helices for lipid-associated KL4. KL4 is helical also in non-lipid environments; in trifluoroethanol it gives a CD spectrum which is similar to that obtained in DPC micelles, and FTIR spectroscopy of KL4 alone, i.e.…”
Section: Secondary Structure Of Kl4 In Phospholipid Micellesmentioning
confidence: 99%
“…interface Spreading kinetics of 2% (w/w) of KL4 in a DPPC/PG/PA 68:22:9 (by weight) mixture at an air/water interface was compared to that of native SP-C and SP-C/BR [20], both with transmembranous c~-helices in similar phospholipid mixtures [11,12,14,26]. KL4 is less efficient than native SP-C and SP-C/BR in accelerating the spreading of the lipid mixture and also reaches a lower surface pressure after 1 min (Fig.…”
Section: Effects Of Kl4 On the Spreading Of Lipids At An Air~watermentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, it could be brought about via global destabilization of the helix with concomitant conversion of a fraction of peptides into a non-helical conformation. The latter explanation appears less likely since non-helical SP-C has a pronounced tendency to aggregate and Vandenbussche et al (1992b) analyzed the secondary structure of depalmitoylated SP-C in phospholipid bilayers after isolation of the peptidellipid vesicles by sucrose density gradient centrifugation, whereby unbound peptides and vesicles containing non-helical/aggregated peptides are expected to be removed. In the NMR structure determination (Johansson et al, 1994b) no NOEs between protons of the palmitoyl groups and the peptide were found.…”
Section: Structures Of the Hydrophobic Proteins Sp-b And Sp-cmentioning
confidence: 99%
“…The procedure used for isolation may affect the structure of at least SP-C, which has been shown to exhibit a tendency to denature and aggregate under various solvent conditions (Ptrez-Gil et al, 1993 ;Johansson et al, 1994bJohansson et al, , 1995a. Furthermore, chemically depalmitoylated SP-C (see below) exhibits a different secondary structure compared to the native lipopeptide (Vandenbussche et al, 1992b;Johansson et al, 1995a) and gives a significantly lower yield on Sephadex LH-60 chromatography (Curstedt et al, unpublished data). Thus, data from studies on SP-C where different isolation procedures have been used may not be directly comparable.…”
Section: Structures Of the Hydrophobic Proteins Sp-b And Sp-cmentioning
confidence: 99%